Clinical manifestations of EVALI in adolescents and the impact of e-cigarettes on the respiratory disease - Hądzlik, Izabela; Piotrowski, Jan; Durowicz, Marcin; Paśnik, Joanna; Sendecka, Gabriela; Kistela, Natalia; Skrzypczak, Katarzyna Oktawia; Krala-Szkaradowska, Magdalena; Stencel, Nicola Joanna; Stuczyński, Sebastian Krzysztof (Journal of Education, Health and Sport, 2024)
In recent years there has been a significant increase in the popularity of electronic cigarettes among adolescents and young adults worldwide. E-cigarettes have reached the market without the extensive preclinical toxicology testing or long-term safety studies required for conventional therapeutics and medical devices. Their effectiveness as a smoking cessation intervention, their impact at the population level and whether they are less harmful than combustible tobacco products are highly controversial. Studies show measurable adverse biological effects on organ and cell health in humans, animals and in vitro. E-cigarette use also increases the risk of respiratory diseases such as chronic obstructive pulmonary disease (COPD) and asthma. There is a serious risk of complications associated with e-cigarette use, such as EVALI (E-cigarette or Vaping Product Use-Associated Lung Injury) - serious lung damage associated with, especially for adolescents. This paper reviews the effects of e-cigarettes on respiratory health.